How Do You Touch an Impossible Thing? - Nicholls, David A. (Frontiers in Rehabilitation Sciences, 2022)
How, and how much, physiotherapists should touch in practice is once again being debated by the profession. COVID and people’s enforced social isolation, combined with the growth of virtual technologies, and the profession’s own turn away from so-called ‘passive’ therapies, has placed therapeutic touch once again in an uncertain position. The situation is more ambiguous and uncertain because, despite its historical importance to the profession, physiotherapists have never articulated a comprehensive philosophy of touch, taking-for-granted its seeming obviousness as either a bio-physical of inter-subjective phenomenon. But both of these approaches are limited, with one failing to account for the existential and socio-cultural significance of touch, and the other rejecting the reality of the physical body altogether. And both are narrowly humanistic. Since touch occurs between all entities throughout the cosmos, and human touch makes up only an infinitesimally small part of this, physiotherapy’s approach to touch seems paradoxically to be at the same time both highly reductive and ontologically vague. Given physiotherapists’ much vaunted claim to be experts in therapeutic touch, it would seem timely to theorise how touch operates and when touch becomes therapeutic. In this paper I draw on Gilles Deleuze’s machine ontology as a new way to think about touch. Critiquing existing approaches, I argue that machine ontology provides a more robust and inclusive philosophy of touch, pointing to some radical new possibilities for the physical therapies.